(untitled) (Architecture Image Studies, 2025)
To achieve the national greenhouse gas reduction target for 2030, buildings are being designed with improved thermal insulation performance to reduce heating and cooling energy consumption. In line with this, regulations on thermal insulation performance are being strengthened, and buildings are becoming increasingly airtight. However, indoor air pollution is increasing due to pollutant emissions from building materials and insufficient ventilation. This study examined the characteristics of a cementitious composite with varying replacement ratio of calcium silicate and zeolite. The results showed that as the replacement ratio of calcium silicate and zeolite increased, thermal insulation and adsorption performance tended to improve. When the zeolite replacement ratio was 5%, the flexural strength was measured at 4.2 MPa, satisfying the minimum flexural strength requirement set by KS standards, and was therefore selected as the optimal mix.